Исследование генопротекторных свойств масел из плодов и листьев Fagus orientalis Lipsky - Агабейли, Р.А.; Мирзазаде, Г.Г. (Цитология и генетика, 2011)
Установлена антимутагенная активность масел, полученных из плодов и листьев бука восточного Fagus orientalis, их способность предотвращать спонтанные и индуцированные химическими мутагенами и старением аберрации хромосом в клетках Allium cepa L., Triticum aestivum L., Vicia faba L., крыс линии Вистар, а также генные мутации у Arabidopsis thaliana. Встановлено антимутагенну активність масел, отриманих з плодів та листя бука східного Fagus orientalis, їхню здатність попереджати спонтанні та індуковані хімічними мутагенами та старінням аберації хромосом в клітинах Allium cepa L., Triticum aestivum L., Vicia faba L., щурів лінії Вістар, а також генні мутації у Arabidopsis thaliana. The antimutagenic activities of the oils obtained from leaves and fruits of Fagus orientalis have been shown in experiments with spontaneous and mutagen" and ageing-induced variability. The aberrations of chromosomes in the meristematic cells of the Allium cepa L, Vicia faba, Triticum aestivum L., and marrow cells of Vistar rats as well as Arabidopsis thaliana gene mutations have been mobilized as experimental tests.